2018
DOI: 10.1039/c8dt02521e
|View full text |Cite
|
Sign up to set email alerts
|

The updated Zn–Sb phase diagram. How to make pure Zn13Sb10(“Zn4Sb3”).

Abstract: The Zn-Sb system contains two well-known thermoelectric materials, Zn1-δSb and Zn13-δSb10 ("Zn4Sb3"), and two other phases, Zn9-δSb7 and Zn3-δSb2, stable only at high temperatures. The current work presents the updated phases diagram constructed using the high-temperature diffraction studies and elemental analysis. All phases are slightly Zn deficient with respect to their stoichiometric compositions, which is consistent with their p-type charge transport properties. Either at room or elevated temperatures, Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Measurements on further samples showed insignificant variations of the composition that lie in the stability range of Zn 13−δ Sb 10 with δ = 0.22−0.38. 26 For the sake of simplicity, the composition of our samples is given as Zn ∼12.8 Sb 10 . SEM images of typical samples (Figure S4) do not show impurity phases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurements on further samples showed insignificant variations of the composition that lie in the stability range of Zn 13−δ Sb 10 with δ = 0.22−0.38. 26 For the sake of simplicity, the composition of our samples is given as Zn ∼12.8 Sb 10 . SEM images of typical samples (Figure S4) do not show impurity phases.…”
Section: Resultsmentioning
confidence: 99%
“…11 Much work has been devoted to the determination of the exact composition of this phase and showed that the nonstoichiometric description Zn13-δSbx (δ = 0.28 -0.38) is more realistic than the classical formula Zn4Sb3. 19,20,21 At room temperature (RT), β-Zn13-δSb10 crystallizes in space group R 3c with two different atom positions for Sb -III and dumbbells with Sb -II as shown in Fig. S1 (S denotes Figures and Tables in the Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,26] Despite all the efforts, [113][114][115][116][117][118] the thermal stability of Zn 4 Sb 3 is still the main concern for practical applications. Lo et al [119] provide a comprehensive study regarding the phase relationship and phase transformation for the binary Zn-Sb system. The phase boundary mapping and phase diagram engineering illustrate the relationship between TE performance and phase stability for the doped Zn 4 Sb 3 .…”
Section: Zn 4 Sb 3 -Based Alloysmentioning
confidence: 99%
“…Aside from the interest in the excellent thermoelectric properties, the extreme structural diversity of the zinc-antimony binary phase diagram has also been intensively investigated. Recently, Lo et al (2018) updated the Zn-Sb phase diagram, and White et al (2018) explored the Li-Zn-Sb phase diagram using a solution-phase method. It is now established that there exists a large number of unique Zn-Sb phases within a narrow compositional range (50-60 at% Zn) including ZnSb (Telkes, 1947), Zn 8 Sb 7 (Pomrehn et al, 2011;Wang & Kovnir, 2015), Zn 9 Sb 7 (He et al, 2015), Zn 4 Sb 3 (Caillat et al, 1997) and Zn 3 Sb 2 (Lo et al, 2017;Boströ m & Lidin, 2004).…”
Section: Introductionmentioning
confidence: 99%